Controversial Discourses: A Critical Examination of Western Philosophy - Hassan, Mohamed Rage (International Journal of Global Sustainable Research, 2024)
This review paper explores key themes in Western philosophy, addressing questions on logic, epistemology, and metaphysics. It emphasizes the diverse influences on philosophy, including cultural and historical factors. The evolution of philosophy, its subjective classification, and the contrasting views on history by Hegel and Hume are discussed. Wittgenstein's pragmatic philosophy, Heidegger's three-fold structure, and Husserl's self-evidence contribute to understanding being. The examination of idealism, metaphysics, and human consciousness reveals philosophical complexities. In conclusion, philosophy shapes human knowledge, integrating the visible and invisible worlds, and continues to evolve, fostering a dialogue about the nature of reality.